New insights into the Saccharomyces cerevisiae fermentation switch: Dynamic transcriptional response to anaerobicity and glucose-excess - van den Brink, Joost (BioMed Central, 2008)
BACKGROUND: The capacity of respiring cultures of Saccharomyces cerevisiae to immediately switch to fast alcoholic fermentation upon a transfer to anaerobic sugar-excess conditions is a key characteristic of Saccharomyces cerevisiae in many of its industrial applications. This transition was studied by exposing aerobic glucose-limited chemostat cultures grown at a low specific growth rate to two simultaneous perturbations: oxygen depletion and relief of glucose limitation. RESULTS: The shift towards fully fermentative conditions caused a massive transcriptional reprogramming, where one third of all genes within the genome were transcribed differentially. The changes in transcript levels were mostly driven by relief from glucose-limitation. After an initial strong response to the addition of glucose, the expression profile of most transcriptionally regulated genes displayed a clear switch at 30 minutes. In this respect, a striking difference was observed between the transcript profiles of genes encoding ribosomal proteins and those encoding ribosomal biogenesis components. Not all regulated genes responded with this binary profile. A group of 87 genes showed a delayed and steady increase in expression that specifically responded to anaerobiosis. CONCLUSION: Our study demonstrated that, despite the complexity of this multiple-input perturbation, the transcriptional responses could be categorized and biologically interpreted. By comparing this study with public datasets representing dynamic and steady conditions, 14 up-regulated and 11 down-regulated genes were determined to be anaerobic specific. Therefore, these can be seen as true "signature" transcripts for anaerobicity under dynamic as well as under steady state conditions.